SCOPE ON BIM AS A TOOL FOR DESIGNING ARCHITECTURAL PROJECTS FOR ARCHITECTS AND ENGINEERS. CASE OF ALGERIA - Khalid Zaouia,; Said Mazouz, (International Journal of Innovative Technologies in Social Science, 2024)
Building Information Modeling, often known as BIM, is considered an indispensable component of the design and construction process in many nations throughout the world. In order to analyze the practitioners' perceptions of BIM's influence on construction in connection to the many tools and software, surveys were carried out and analyzed with the sphinx tool. The surveys were also carried out to determine the architects' and engineers' capacities to integrate BIM into their design processes. Despite having limited understanding about BIM as a new method of work, the results indicated that both architects and engineers are concerned about improving design processes in order to provide a higher level of quality to the projects they are working on in Algerian context.